Efficient contracts for government intervention in promoting next generation communications networks - Wolfgang Briglauer; Christian Holzleitner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Although the future socio-economic benefits of a new fibre-based ('next generation access', NGA) telecommunications infrastructure seem to be uncontroversial, a universal NGA coverage appears to be a rather unrealistic objective without government intervention. We contend, however, that the current contract practice of fixing ex ante targets for network expansion is inefficient given the uncertainty about future returns on NGA infrastructure-based services and the public authorities' incomplete information about the capital costs of the network provider. This paper puts forward to delegate the choice of the network expansion to the NGA provider.
urn:nbn:de:bsz:180-madoc-366306
Keywords: H20; L43; L44; L51; L52; L96; 330; contract theory; public utilities; next generation telecommunications networks; subsidies